Identifikasi Potensi Bahaya Kerja Dalam Usaha Meningkatkan Produktivitas Dengan Pendekatan Fault Tree Analysis Pada Produksi Tahu - Lindu Aji Pranmestya; Ayudyah Eka Apsari (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
Occupational safety and health (K3) programs are important in maintaining the physical condition and cooperative attitude of employees within the company. Law No. 1 of 1970 regulates the importance of protecting work safety for every worker. UMKM tofu owned by Mr. Kadek, a micro and small industry, faces challenges in implementing OSH for its workers. The humid and slippery working environment, the risky waste disposal system, and the lack of use of personal protective equipment (PPE) cause accidents and illnesses for workers. The results of the interviews indicated that there were significant work accident cases, which had an impact on decreasing employee productivity and income levels. The rate of work accidents at MSMEs knows Mr Kadek has increased significantly from 2021 to 2022. The frequency of accidents has increased from 577 to 915 per million hours worked, while the severity of disability injuries has increased from 2,090 to 2,820. The impact of work accidents also affects work productivity. In 2022, there will be an increase in the number of working hours lost due to accidents, namely 154 hours. This shows that frequent work accidents have a negative impact on productivity levels. The high rate of work accidents also negatively affects the company's downfall. Improvements are needed in the application of OSH, such as ergonomics training, active supervision, waste management, personal protection, facility improvements, and safety awareness. In this case, Fault Tree Analysis is used to identify the causes of work accidents. In order to increase the level of productivity and employee safety, it is necessary to have a K3 improvement program in MSMEs, Mr. Kadek knows.